2014
DOI: 10.3109/13880209.2014.918157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signalings in keloid disease and current therapeutic approaches from natural based compounds

Abstract: The present review may be helpful to future studies that further examine the molecular mechanism of keloid etiology as well as investigate the anti-keloid property in natural compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…In recent years, the relationship between insulin-like growth factor (IGF)-1 and the scar has received increasing attention [15]. Studies displayed that the expression of IGF-1 in the wound area was upregulated after the injury of cornea, skin and other tissues [16], and exogenous IGF-1 could improve the healing of skin and wounds [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the relationship between insulin-like growth factor (IGF)-1 and the scar has received increasing attention [15]. Studies displayed that the expression of IGF-1 in the wound area was upregulated after the injury of cornea, skin and other tissues [16], and exogenous IGF-1 could improve the healing of skin and wounds [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (8) found 250 upregulated and 152 downregulated genes in keloid compared with normal skin. Moreover, several signaling pathways and transcriptional factors are found associated (9,10). However, the precise linkage gene and pathological process are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…R epresenting the extreme end of the cutaneous scarring spectrum, keloid disease is a fibroproliferative tumour characterised by excess extracellular matrix (ECM) deposition, increased inflammatory cytokine expression and aggressive local invasion (1). Although keloid is often referred to as benign, in that it does not metastasize, it behaves in a tumorigenic fashion by actively invading adjacent normal skin and spreading beyond the boundaries of the original wound (2,3). To date, although significant progress has been made, the mechanisms underlying the migration required for keloid invasion have not been fully elucidated.…”
mentioning
confidence: 99%